Influence of tibial plateau levelling osteotomy on the tensile forces sustained by ligaments in cranial cruciate ligament‐intact canine stifles: An ex vivo pilot study. Issue 5 (10th August 2022) - Shimada, Masakazu; Takagi, Tetsuya; Kanno, Nobuo; Yamakawa, Satoshi; Fujie, Hiromichi; Hara, Yasushi
Abstract: Background: Tibial plateau levelling osteotomy (TPLO) changes the anatomical tibial conformation and might alter the positional relationship of the ligaments comprising the stifle joint. As a result, it is expected to affect the tensile force of the ligaments. However, studies analyzing the details of the effect of osteotomy are limited. Objectives: To evaluate the influence of TPLO on the tensile force on the stifle ligaments in the intact canine stifle using a six‐degree‐of‐freedom (6‐DOF) robotic testing system. Methods: Eight stifles were categorised into the reference group and nine stifles into the TPLO group. The stifles were then analysed using a 6‐DOF robotic joint biomechanical testing system. The stifles were applied 30 N at cranial, caudal, and compression loads and 1 Nm at the internal and external torque loads (the load applied to the tibia relative to the femur) on extension, at 135° and 120°, respectively. The tensile force placed on the cranial cruciate ligament (CrCL), the caudal cruciate ligament, the medial collateral ligament, lateral collateral ligament and the total tensile force placed on the four ligaments was calculated under each load. Results: For the caudal load applied to the tibia relative to the femur, the CrCL tensile force in the TPLO group was lower than that in the reference group at 120° ( p  = 0.02). The CrCL tensile force in the TPLO group was lower than that in the reference group at 120° ( p  < 0.01) for the compression load. Regarding the cranial, internal, and external load, the CrCL tensile force remains unchanged between both groups at each angle. Conclusions: TPLO reduces CrCL tensile force during compression and caudal force application. TPLO may reduce tensile forces contributing to CrCL rupture. Abstract : The aim of the study is to evaluate the influence of tibial plateau levelling osteotomy on the tensile force on the stifle ligaments in the intact canine stifle using a six‐degree‐of‐freedom robotic testing system. The results suggest that tibial plateau levelling osteotomy reduces the cranial cruciate ligament tensile force during compression and caudal force application.